Penguatan Keterampilan Profesional Mahasiswa melalui Program Mini Riset Kunjungan Industri - Fanggidae, Ronald P.C; Aryono, Muhamad Dian (Welfare : Jurnal Pengabdian Masyarakat, 2025)
A significant challenge faced by higher education today is the gap between academic theory learned by students and the practical skills required in the workforce. To bridge this gap, the Management Study Program at Universitas Nusa Cendana conducted a mini research industrial visit program to five companies in Kupang City. The program aimed to provide real-world experience through direct observation and in-depth interviews with management representatives about operational management, production processes, quality control, and distribution strategies. Students were divided into groups and tasked with compiling visit reports, which were then presented and discussed collectively. The results of the activity showed an increase in students’ understanding of managerial practices, as well as strengthening their analytical, communication, and teamwork skills. Evaluation through questionnaires and participant testimonies indicated that the activity had a positive impact on preparing students for the workforce. This program has proven effective as a contextual and adaptive learning model.